The impact of power and relationship commitment on the integration between manufacturers and customers in a supply chain - Zhao, Xiande; Huo, Baofeng; Flynn, Barbara B.; Yeung, Jeff Hoi Yan (Journal of Operations Management, 2008)
Supply chain integration (SCI) has received increasing attention from scholars and practitioners in recent years. However, our knowledge of what influences SCI is still very limited. Although marketing and management researchers have investigated power and relationship commitment issues between organizations, few have examined their impact on SCI. This paper extends the power–relationship commitment theory established in Western marketing literature and links it with SCI in China, through examining the relationship between power, relationship commitment and the integration between manufacturers and their customers. We propose and empirically test a model using data collected from 617 manufacturing companies in China. The results show that different types of customer power impact manufacturers’ relationship commitment in different ways. Expert power, referent power and reward power are important in improving manufacturers’ normative relationship commitment, while reward power and coercive power enhance instrumental relationship commitment. We also found that normative relationship commitment had a greater impact on customer integration than instrumental relationship commitment. These findings are interpreted in light of national culture differences between China and the U.S. in terms of power distance and collectivism, which provide a new perspective on SCI.